The Impact of Islamic Philanthropic Mechanisms on Poverty Alleviation and Economic Resilience in the Wake of Fuel Subsidy Removal in Nigeria - Mikail, Usman Jibril; Muhammad, Adamu Abubakar; Babangida, Bala; Tijjani, Abdulkareem Ahmad; Adam, Maryam (IDRIS Darulfunun Institute, 2025)
-